Civic Competence as a Target Component of Education Content - Gayane Poghosyan (BIRCU, 2019)
Nowadays it is a necessity to include the competence to the target component of education content.An individual and socially significant activity of real-world objects should be interconnected with the other target components of content and based on experience as a social requirement/Khutorskoy A.V, 2013. Civic competence is represented as: the unity of civil competence of the subject (Zimnyaya I.A.,2006), the unity of readiness and abilities, which allows the active, effective and responsible control of the rights and duties of a member of a democratic society, applying the knowledge and skills and civic qualities.The issue of development of civil competence was always faced teachers almost in all countries and was considered only as a pedagogical activity, and not as the educational problem.For the formation of civic competence, it is necessary first of all to form the abilities of both students and teachers who can make decisions in different living conditions - in different training situations (self-education) they can make decisions, identify problems and give solutions, as well as purposeful and responsible actions, at the same time developing creative and critical thinking.